Political and Religious Expressions of Gen Z Muslims in islami.co’s Instagram Comic Strips - Abraham Zakky Zulhazmi; Andi M. Faisal Bakti (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study aims to analyze the political and religious expressions of Muslim Generation Z as represented on the Instagram account of islami.co. Methodology: The research employs a qualitative approach using semiotic analysis to examine selected comic strips. Data were collected through virtual ethnography by gathering comic strip posts published on the islami.co Instagram account. Findings: The study finds that the comic strips shared by islami.co on Instagram serve as representations of the political and religious expressions of Muslim Gen Z in response to political events in Indonesia. The comics reflect a form of critical Islam, particularly in relation to the then-ongoing presidential election. Research Implications: This research contributes to the growing body of scholarship on Islam in digital spaces, particularly as expressed through visual media like comics. It recommends the production of more progressive Islamic content on social media to help foster critical thinking among young Muslims. Such content should be delivered in popular formats such as comics, podcasts, vlogs, and similar media. Originality/Value: This study offers a novel contribution by integrating the themes of comics, politics, and religion within the framework of social media studies and Muslim Gen Z identity.